Advances in Direct Injection Reciprocating Internal Combustion Engines (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Reciprocating internal combustion engines (RICEs) are the most robust and efficient machines to cover ground and marine transport demands. Worldwide road transport and off-road power needs will continue being successfully satisfied by this type of thermofluid machines in the short- to mid-term. Alternatives are still immature to both effectively deal with global warming and offer the performance expected by customers. Governmental regulations are wisely limiting more and more greenhouse gases (CO2) and any harmful emissions; forcing engineering and scientific communities to push the efficiency and to reduce the pollution from RICEs, until they are eventually limited to below the background. This scenario has offered exciting opportunities in the last few years to engineers and researchers to investigate new ideas and technologies. The second revolution of the RICEs is here: Direct injection, multi-reactivity fuels, gases aftertreatment, and turbocharging are presently the baseline to further progress. These techniques are offering an extraordinarily high level of control of emissions in any operative condition. A change in paradigms is surprising the engineers with figures of efficiency overcoming the limits day after day. This book compiles a selection of research papers discussing critical aspects related to the new generation of RICEs.